Cutaneous metastatic seeding as a sequela of nephrostomy catheter placement - Kavya Mirchia, MD; Kanish Mirchia, MD; Ryan Thibodeau, MPH; Abtin Jafroodifar, MD; Atin Goel, MD; Mohammad Jawed, MD (Radiology Case Reports, 2021)
Urothelial carcinoma and nephrolithiasis are a common cause of obstructive uropathy which can be relieved by percutaneous nephrostomy catheter placement. A rare, but known complication of this procedure is iatrogenic seeding of tumor cells along the nephrostomy tract. We describe a case of 68-year-old-female with cutaneous metastasis of high-grade urothelial carcinoma with seeding of tumor cells along the percutaneous nephrostomy catheter tract 8 months after the removal of the catheter. Given its severity, interventional radiologists should be mindful of the number of percutaneous access attempts, exchanges, and catheter manipulations in patients with urothelial carcinoma due to the risk of metastatic seeding along the percutaneous tract or to nearby tissues.